Practical Impairments in FBG-Based True Time Delays - Costanzo Caso, Pablo Alejandro (2012)
In this paper we analyze the response of a non-ideal optical beamforming system which employs true-time delays based on fiber Bragg gratings. Effects regarding deviation of the Bragg wavelengths, instabilities of the laser source wavelength and misalignment of the fiber path lengths, were studied. We show how these deviation parameters affect the irradiation pattern of linear phased-array antennas.